Development of evidence-based indicators for the detection of drug-related problems among ovarian cancer patients - Kala Bahadur Rawal; Uday Venkat Mateti; Vijith Shetty; Chakrakodi Shashidhara Shastry; Mazhuvancherry Kesavan Unnikrishnan; Shraddha Shetty; Aparna Rajesh (Frontiers Media S.A., 2023)
Background: Antineoplastic drugs produce serious drug-related problems and their management is challenging. DRPs are critical, for saving on therapeutic costs, particularly in resource poor settings within low-middle-income countries such as India. Indicators are clues that helps to detect DRPs within the healthcare organization and minimize overall harm from medications. Indicators enable healthcare professionals to determine the future therapeutic course. And enable healthcare professionals to take a proactive stand, and stay informed and empowered to both prevent and manage DRPs. This study aims to develop evidence-based indicators for detecting potential drug-related problems in ovarian cancer patients.Patients and Methods: A retrospective study was conducted in the Department of Oncology of a tertiary care teaching hospital in South India. Based on literature search, we developed a list of indicators, which were validated by a Delphi panel of multidisciplinary healthcare professionals (16 members). Based on 2 years of ovarian cancer data, we performed a feasibility test retrospectively and classified the DRPs according to the Pharmaceutical Care Network Europe classification of DRPs version-9.1.Results: The feasibility test identified 130 out of 200 indicators. A total of 803 pDRPs were identified under four main categories: drug selection problem, drug use problem, adverse drug reaction and drug-drug interaction The most frequently observed were ADR 381 (47.45%), DDIs 354 (44.08%), and drug selection problems 62 (7.72%).Conclusion: Indicators developed by us effectively identified pDRPs in ovarian cancer patients, which can potentially help healthcare professionals in the early detection, timely management, and attenuating severity of DRPs. Identifying the pDDIs can potentially improve interdisciplinary involvement and task sharing, including enhanced pharmacists' participation within the healthcare team.